2012
DOI: 10.1128/cvi.05553-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Recombinant Multiepitope Peptide for Serodiagnosis of Toxoplasma gondii Infection

Abstract: bDetection of Toxoplasma gondii infection with sensitive and specific methods is a key step in the prevention and treatment of toxoplasmosis. Among the available diagnostic tests, serology is commonly used. Although serological tests give satisfactory results, the production of reliable reagents remains laborious and expensive. There is therefore a real need to acquire specific and effective recombinant antigens for the serodiagnosis of T. gondii infection. In this study, a multiepitope peptide was designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 31 publications
2
64
0
Order By: Relevance
“…However, producing specific and standard antigens is a real challenge. Currently, most commercial serological kits use crude Toxoplasma antigens prepared through mouse passages or cell culture systems [29,30]. The soluble native antigen of T. gondii parasite has been applied as a diagnostic marker in various seroepidemiological studies [4], a researcher used crude native antigen of type I and II, for example [1].…”
Section: Production Of Reliable and Standard Antigen For Serological mentioning
confidence: 99%
See 4 more Smart Citations
“…However, producing specific and standard antigens is a real challenge. Currently, most commercial serological kits use crude Toxoplasma antigens prepared through mouse passages or cell culture systems [29,30]. The soluble native antigen of T. gondii parasite has been applied as a diagnostic marker in various seroepidemiological studies [4], a researcher used crude native antigen of type I and II, for example [1].…”
Section: Production Of Reliable and Standard Antigen For Serological mentioning
confidence: 99%
“…The epitope is classified into two categories based on their primary structure: linear (continuous) epitope if the amino acids sequences in the epitope are continuous or conformational (discontinuous) epitope which composed from discontinuous sections of amino acid [46]. Attempts to achieve high sensitive and specific diagnostic assay usually assume that replacing the native antigen in all current diagnostic kits by standard and reliable reagents can significantly increase the assay performance [30]. In recent years, it has been demonstrated that the use of peptide-based antigen can meet the demand to standardize the serodiagostic test of toxoplasmosis and increase the sensitivity and specificity of these assays.…”
Section: Epitope-based Antigenmentioning
confidence: 99%
See 3 more Smart Citations